City Information Models (CIMs) as precursors for Urban Digital Twins (UDTs): A case study of Lancaster - Cureton, Paul; Hartley, Elliot (Frontiers in Built Environment, 2023)
City Information Models (CIMs) have several research challenges present as part of a roadmap for transition to Urban or City Digital Twins (UDTs/CDTs) and broader Smart Cities. In a period of digital transformation in urban planning, CIMs are primarily designed to intersect and merge urban GIS/BIM, termed GeoBIM (Laat & van Berlo, 2011). The current state of the art of CIMs is that they are often cloud-based geospatial services and data repositories with one-way data connections (Souza, 2022), which differ from the integrated, high fidelity. Cyber-physical complex systems for Digital Twins (DTs) (Ketzler et al., 2020). Four broad socio-technical research challenges are present to progress CIMs toward full UDTs/CDTs, including 1. Technical training for adoption, 2. Acquisition strategies for aerial data and remote sensing 3. Data licensing types and system management, and 4. Stakeholder engagement with CIM platforms. These four research challenges and digital transformation are discussed and explored in the Lancaster City Information Model (LCIM) case study. The LCIM was developed for architects, planners and stakeholders to engage with 3D urban models and urban analytics (view sheds, masterplan scenarios and solar potentials of buildings) from 2019-2021. Results were used to inform governance in co-designed workshops resulting in the most extensive 3D open urban dataset published in the UK, consisting of a baseline of 1"+/- buildings and infrastructure and 7.5cm aerial imagery. The delivery of this case and the resulting published dataset highlights essential research on these four complex challenges to deliver full DT ambitions and digital transformation.